Classification and genetic counselling for a novel splicing mutation of the MLH1 intron associated with Lynch syndrome in colorectal cancer. (6th September 2021) - Wang, Ling-Ling; Zou, Shuang-Mei; Dong, Lin; Yang, Ming; Qi, Dan; Lu, Zhao; Chen, Jia-Nan; Mei, Shi-Wen; Zhao, Zhi-Xun; Guan, Xu; Jiang, Zheng; Liu, Qian; et al.
Abstract: Background: Lynch-syndrome-associated cancer is caused by germline pathogenic mutations in mismatch repair genes. The major challenge to Lynch-syndrome screening is the interpretation of variants found by diagnostic testing. This study aimed to classify the MLH1 c.1989 + 5G>A mutation, which was previously reported as a variant of uncertain significance, to describe its clinical phenotypes and characteristics, to enable detailed genetic counselling. Methods: We reviewed the database of patients with Lynch-syndrome gene detection in our hospital. A novel variant of MLH1 c.1989 + 5G>A identified by next-generation sequencing was further investigated in this study. Immunohistochemical staining was carried out to assess the expression of MLH1 and PMS2 protein in tumour tissue. In silico analysis by Alamut software was used to predict the MLH1 c.1989 + 5G>A variant function. Reverse transcription-polymerase chain reaction and sequencing of RNA from whole blood were used to analyse the functional significance of this mutation. Results: Among affected family members in the suspected Lynch-syndrome pedigree, the patient suffered from late-stage colorectal cancer but had a good prognosis. We found the MLH1 c.1989 + 5G>A variant, which led to aberrant splicing and loss of MLH1 and PMS2 protein in the nuclei of tumour cells. An aberrant transcript was detectable and skipping of MLH1 exon 17 in carriers of MLH1 c.1989 + 5G>A was confirmed. Conclusions: MLH1 c.1989 + 5G>A was detected in a cancer family pedigree and identified as a pathological variant in patients with Lynch syndrome. The mutation spectrum of Lynch syndrome was enriched through enhanced genetic testing and close surveillance might help future patients who are suspected of having Lynch syndrome to obtain a definitive early diagnosis.